Marx - Barnett, Vincent (Routledge, 2009)
Karl Marx has been portrayed in equal measure both as a political prophet who foresaw the end of capitalist exploitation, and as a populist Anti- Christ whose totalitarian legacy has cost millions of lives worldwide. This new biography looks beyond these caricatures in order to understand more about the real Karl Marx; about his everyday life and personal circumstances as well as his political ideology.